2019
DOI: 10.5933/jkapd.2019.46.2.226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano-filled Protective Coating on Microhardness and Wear Resistance of Glass-ionomer Cements

Abstract: The purpose of this study was to investigate the effect of adding a protective coating on the microhardness and wear resistance of glass ionomer cements (GICs). Specimens were prepared from GIC and resin-modified GIC (RMGI), and divided into 3 groups based on surface protection: (1) no coating (NC), (2) Equia coat coating (EC), and (3) un-filled adhesive coating (AD). All specimens were then placed in distilled water for 24 h. Surface hardness (n = 10) was evaluated on a Vickers hardness testing machine. Wear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…While Bonifacio et al [30], showed significant improvement in the wear resistance of Fuji IX GP Extra when G-Coat Plus was applied, Kielbassa et al 's [31] findings on Equia coating supports our outcome by showing a lack of effective long-term protection against abrasive wear for Equia coat. Our finding is also in agreement with that of Rye et al [32] who reported no statistically significant differences in the wear resistance between coated and uncoated GICs. Moreover, Bertrand et al [33] revealed that the application of resin coating caused decreased microhardness of the composite resin's surface.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…While Bonifacio et al [30], showed significant improvement in the wear resistance of Fuji IX GP Extra when G-Coat Plus was applied, Kielbassa et al 's [31] findings on Equia coating supports our outcome by showing a lack of effective long-term protection against abrasive wear for Equia coat. Our finding is also in agreement with that of Rye et al [32] who reported no statistically significant differences in the wear resistance between coated and uncoated GICs. Moreover, Bertrand et al [33] revealed that the application of resin coating caused decreased microhardness of the composite resin's surface.…”
Section: Discussionsupporting
confidence: 94%
“…However, the study did not use an uncoated control group in their methodology, and thereby, their conclusion may not be as reliable. In other work by Ryu et al [ 32 ] on Equia coat, the authors reported an increase in wear resistance followed by surface protection. The difference in the tested coating as well as fewer chewing cycles implemented in their study may explain the contradictory finding.…”
Section: Discussionmentioning
confidence: 84%
“…While Bonifacio et al [29], showed signi cant improvement in the wear resistance of Fuji IX GP Extra when G-Coat Plus was applied, Kielbassa et al's [30] ndings on Equia coating supports our outcome by showing a lack of effective long-term protection against abrasive wear for Equia coat. Our nding is also in agreement with that of Rye et al [31] who reported no statistically signi cant differences in the wear resistance between coated and uncoated glass ionomer cements. Moreover, Bertrand et al [32] revealed that the application of resin coating caused decreased microhardness of the composite resin's surface.…”
Section: Discussionsupporting
confidence: 93%
“…However, the study did not use an uncoated control group in their methodology, and thereby, their conclusion may not be as reliable. In other work by Ryu et al [31] on Equia coat, the authors reported an increase in wear resistance followed by surface protection. The difference in the tested coating as well as fewer chewing cycles implemented in their study may explain the contradictory nding.…”
Section: Discussionmentioning
confidence: 78%
“…These findings are consistent with those of Kunzelmann et al, 21 who discovered that Fuji IX had the least amount of material loss when compared to Ketac Silver and Ketac Molar. Ryu et al 22 looked at the wear resistance of several GICs and found a substantial difference in early wear rates as well as a considerable decrease in long-term wear rates. Within the time frame of 4 months to 1 year, however, evidence of wear reduction was also detected.…”
Section: Discussionmentioning
confidence: 99%